تأثير حصول المنظمات على شهادة المطابقة للمواصفة الدولية 9001:2008على رضا المستهلكين. (دراسة ميدانية على مستهلكي منتجات الشركات الصناعية العاملة في محافظة اللاذقية) - زاهر بسام; جبور وسيم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة إلى التعرف على تأثير حصول المنظمات على شهادة المطابقة للمواصفة الدولية ISO 9001:2008على رضا المستهلكين في الشركات الصناعية في محافظة اللاذقية, واعتمد الباحث على المقاربة الاستنباطية كمنهج عام للبحث, وقام الباحث بتوزيع الاستبيان على (340) مستهلك من مستهلكي منتجات هذه الشركات, وخلصت النتائج إلى وجود فروق معنوية إيجابية بين حصول الشركات محل الدراسة على شهادة ISO 9001:2008 ورضا المستهلك (شكاوى المستهلك, الإقبال المتكرر على الشراء, تكوين اتجاهات إيجابية للشراء, الجودة المدركة من قبل المستهلكين والجودة المقدمة من الشركات), ثم قدمت الدراسة بعض التوصيات والتي كان من أهمها: وجوب الاهتمام بشكاوى المستهلكين, والتركيز على أبعاد جودة المنتجات المقدمة للمستهلكين. This study aimed to identify the impact of organizations obtain the certificate of conformity for International Standard ISO 9001: 2008 on Consumers satisfaction in industrial companies satisfaction in Latakia province, And it adopted a researcher on the approach Alastenbatih as a way in to search, And it has distributed a questionnaire to 340 individual consumers of products from these companies,And it found the results to a positive significant differences between for companies under study, on ISO 9001: 2008 certification and consumer satisfaction (consumer complaints, repeated demand for the purchase, configure the positive trends to buy, the quality perceived by consumers and quality provided by the companies), And then offer some suggestions and recommendations, which was the most important: should interest complaints made by consumers, and focus on the quality of products offered to consumers dimensions.